What Stakeholders Need from their Undergraduate University English Courses - Laura Molina; Fernando Fernández (Praxis & Saber)
This article is based on the results of a master’s dissertation entitled A Needs Analysis into the Compulsory English Courses of South Colombian University (USCO). This study has three aims: first, to identify the disfavouring conditions that teachers consider to be affecting the courses in question; second, to identify a possible gap between the felt needs of current and former students and the English language training which they receive at USCO; and third, to collect suggestions from stakeholder groups for future improvements to the courses. Data was collected through questionnaires and interviews; the participants included current students, former students, teachers, and the supervisor of the courses. The results show that students’ needs are not currently being met and that an English for Specific Purposes approach is required. Teachers face a lack of educational resources and limited cohesion amongst colleagues, while the major problem of the supervisor is that of budgeting.